Development of English materials for sustainable tourism based on technology - Karimullah, Imam Wahyudi; Elfiyanto, Sonny; Mustofa, Mutmainnah; Rijnenberg, Jeroen; Romadhon, M. Galuh Elga; Muchlisin, Muhammad; Barlaman, Moh. Aang Fajar; Humairoh, Septiana Anggun; Syaifullah, Ahmad Fadli; Jazil, Moh.; Aushoth, Ahmad Nawwal Samhan Abu (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2025)
The development of English teaching materials related to sustainable tourism in vocational high schools still faces various challenges, despite the significant growth of the tourism industry in Indonesia. This Community Service Program aims to enhance the teaching abilities of English teachers at vocational high schools in Malang by helping them develop teaching materials that incorporate various aspects of sustainable tourism through an intensive educational and mentoring approach. A total of 20 teachers participated in this workshop and training program. During implementation, they received training to develop online learning materials that simultaneously enhance reading, listening, and writing skills while also providing practice in tour guiding. Additionally, they were trained in utilizing technology to present interactive teaching materials aligned with advancements in the modern tourism industry. As a result, the teachers' ability to develop digital-based learning materials improved significantly, enabling them to guide students more effectively. In line with the teachers' enhanced ability to design innovative and sustainable learning materials, this initiative aims to raise educational standards at the vocational high school level and support students in adapting to advancements in the tourism industry.